ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KOPI ROBUSTA GAYO (Coffea Canephora). Studi Kasus: Pasar Inpres Kecamatan Bebesen, Kab. Aceh Tengah - Yuni Zanesty Hutapea; Siti Mardiana; Mitra Musika Lubis (Universitas Medan Area, 2020)
production. Robusta coffee is coffee derived from the seeds of the Coffea Canephora plant. The purpose of this study was to determine what factors influence the demand for Robusta coffee in the Inpres market, Bebesen sub-district, Kab. Central Aceh. The sampling method is done by the method of tracking (Accidental Sampling). Respondents in this study were consumers who happened to be shopping for Robusta coffee at the study site, which were 52 respondents. The data collected are primary data and secondary data, the analytical method used is multiple linear regression test with SPSS 24 tools. The results of this study conclude that the Robusta coffee expenditure variable, income, number of family members, tastes, expenditure on substitute goods purchases simultaneously has a significant effect on robusta coffee demand in the presidential market. Partially, the income variable significantly influences the demand for Robusta coffee in the Inpres market, while the expenditure variable for Robusta coffee purchase, the number of family members, tastes, and expenditure for substitute goods purchase, does not significantly affect the demand for coffee in the Inpres market